Politikas zinātne: Identitātes maiņa, pārklāšanās un mijiedarbība - Latvijas Universitāte (Latvijas Universitāte, 2005)
This collection of essays explores different aspects of the complex problem of identity, placing special emphasis on ethnic and political identity.
Political science: Changing, overlapping and interacting identities
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science; Identity; Ethnic identity; National identity; Identity change; Political identity; Europeanization; Collective identity; Identitāte; Etniskums; Nacionālā identitāte; Politiskā identitāte